2015
DOI: 10.1016/j.jacc.2015.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dual Lipid-Lowering Strategy With Ezetimibe and Atorvastatin on Coronary Plaque Regression in Patients With Percutaneous Coronary Intervention

Abstract: Compared with standard statin monotherapy, the combination of statin plus ezetimibe showed greater coronary plaque regression, which might be attributed to cholesterol absorption inhibition-induced aggressive lipid lowering. (Plaque Regression With Cholesterol Absorption Inhibitor or Synthesis Inhibitor Evaluated by Intravascular Ultrasound [PRECISE-IVUS]; NCT01043380).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(166 citation statements)
references
References 20 publications
7
136
1
7
Order By: Relevance
“…This result suggests that worsened clinical presentation and vulnerable plaque features at baseline may result in more favorable responses among nonculprit plaques to statin. Similar results were reported in several previous studies using intravascular ultrasonography and OCT 10, 38, 39. Takarada et al demonstrated that the efficacy of statin therapy on improving FCT, assessed by serial OCT, was significantly greater in plaques with thinner caps than in those with thicker caps 10.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This result suggests that worsened clinical presentation and vulnerable plaque features at baseline may result in more favorable responses among nonculprit plaques to statin. Similar results were reported in several previous studies using intravascular ultrasonography and OCT 10, 38, 39. Takarada et al demonstrated that the efficacy of statin therapy on improving FCT, assessed by serial OCT, was significantly greater in plaques with thinner caps than in those with thicker caps 10.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, most studies that tested the efficacy of statin therapy on plaque stabilization in patients with ACS demonstrated improvement in plaque phenotype 10, 11, 40, 41. Recently, Tsujita et al conducted a randomized trial to investigate the efficacy of additional ezetimibe intake over atorvastatin alone on changes in plaque volume over 9 to 12 months of follow‐up 39. They reported that plaque regression in the group treated with additional ezetimibe was greater in the ACS cohort than in the stable angina cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the PRECISE-IVUS (Plaque Regression With Cholesterol Absorption Inhibitor or Synthesis Inhibitor Evaluated by Intravascular Ultrasound) trial found that sterols (lathosterol, campesterol, and sitosterol) and their ratio to cholesterol increased with atorvastatin monotherapy but decreased with the atorvastatin-ezetimibe combination. Interestingly, the campesterol-to-cholesterol ratio reduction was positively related to a reduction in percent atheroma volume [20]. The notion that statin-ezetimibe combination therapy might reduce the variability in LDL-C-lowering response is also supported by a recent analysis of patient-level data pooled from 27 double-blind controlled studies [21].…”
Section: Variability In Individual Response To Statin Therapymentioning
confidence: 86%
“…As expected, the atorvastatin-ezetimibe combination resulted in lower levels of LDL-C than atorvastatin monotherapy (63.2 vs. 73.3 mg/dl; p \ 0.001). More importantly, a significantly greater percentage of patients who received atorvastatin-ezetimibe experienced coronary plaque regression (78 vs. 58%; p = 0.004) [20]. An interesting substudy of this trial showed that achieved LDL-C was the strongest independent predictor of reduction in coronary atheroma volume [79].…”
Section: Impact Of the Atorvastatin-ezetimibe Combination On The Progmentioning
confidence: 89%
“…Az ezetimibbel a 2002-ben történt bevezetése óta számos vizsgálatot végeztek, ezek közül a fentebb részletezett IMPROVE-IT hozott érté-kes evidenciákat: a szer hatékonyan csökkenti a cardiovascularis rizikót, 21%-kal csökkentve az ischaemiás stroke bekövetkeztének esélyét is [27]. Az 50% feletti LDL-C-szint-csökkenést, emellett az ezetimib haté-konyságát támasztotta alá a coronariaplakk-regresszió-ban több vascularis ultrahanggal elvégzett vizsgálat is [29,30].…”
Section: Az Ldl-koleszterin-szint Csökkentésének úJ Irányvonalaiunclassified